Loaders for Concrete Compaction - Nesterenko, Mykola; Panfilov, Olexandr; Pyrlyk, Maxim (Academic journal Industrial Machine Building Civil Engineering, 2023)
The article presents a comprehensive analysis of load applicator designs used in the compaction technologies of stiff and lightweight concrete mixtures. The role of loading is revealed as one of the key factors influencing the effectiveness of forming products made from concrete with a low water-to-cement ratio. The main operating principles of load applicators are described, which apply additional force to the concrete mixture in combination with vibrational loading. A classification of load applicators is provided based on design features and energy source: inertial, non-inertial, pneumatic, and vibratory load applicators. Special attention is given to combined devices that integrate vibrational and impulse action on concrete. The study summarizes research findings that confirm the advantages of combined compaction, particularly when using pneumatic load applicators with adjustable pressure. It has been established that the use of active load applicators allows for a reduction in cement consumption by up to 30%, a decrease in product forming time by up to 50%, improved compaction uniformity along the height, and enhanced surface quality. An original design of an active load applicator with a vibration exciter and impact elements is proposed, providing impulse compaction with adjustable pressure and frequency. The main unresolved aspects of the problem are identified — the lack of unified methodologies for calculating loading parameters, insufficient adaptability of designs to changes in product geometry and concrete mixture properties. The feasibility of developing intelligent controlled load applicators capable of adapting to forming conditions is substantiated to improve the efficiency of reinforced concrete product manufacturing.